Cesiated surface H− ion source: optimization studies. (11th January 2017) - Ueno, Akira
Abstract: The H − ion beam intensity required for high-energy and high-intensity proton accelerators is continuously increasing. The required 95%-beam transverse normalized root mean square emittance ( ε 95%rnms x / y ) of the beam is around 0.25 π mm mrad for all accelerators. The Japan Proton Accelerator Complex (J-PARC) 400 MeV linear accelerator (LINAC) succeeded in accelerating the world's highest-class H − ion beam of 50 mA with a cesiated RF-driven H − ion source. This was achieved by increasing the beam brightness through the following measures: (1) 45°-tapered plasma electrode (PE) with a 16 mm thickness to increase beam intensity by 56%, (2) continuous-wave igniter plasma driven by 50 W 30 MHz RF to reduce hydrogen pressure in the plasma chamber (PCH) by 50% and beam loss in low-energy beam transport by 12%, compared with that by the commonly used 300 W 13.56 MHz RF, (3) axial magnetic-field correction around the PE beam aperture to increase beam intensity by a maximum of 15%, (4) operation at a low PE temperature ( T PE ) of about 70 °C to reduce ε 95%nrms x / y by 27%, (5) suitable beam apertures of the plasma and the extraction electrodes to increase beam intensity by a maximum of 7% and to reduce ε 95%nrms x / y by more than 4%, (6) argon/nitrogen elimination and 39% filter-field reduction to reduce ε 95%nrms x / y by 9% and the required 2 MHz RF power by around 30%, (7) eight-hours conditioning with a 50 kW 2 MHz RF and a 5% (1 ms × 50 Hz) duty factor to reduce ε 95%nrms x / y by 15%, and (8) slight water molecules (H2 Os) feeding in hydrogen to avoid ε 95%nrms x / y increase by 72% and divergence angle expansion by 50%. In the studies, we investigated principally the 66 mA H − ion beams extracted from the source in order to achieve a 50 mA beam at the J-PARC LINAC exit regardless of the beam's brightness. Consequently, the source can produce the required beam for a 60 mA J-PARC LINAC operation, since the world's brightest-class beam with the ε 95%nrms x / y of 0.23 π mm mrad and beam intensity of 66 mA is successfully produced through the above measures.